The Abbasid Revolution 747-750 and The Iranian Revolution 1978-1979: A Comparative Perspective - Hassan, Ali Bakr (Journal of Al-Tamaddun, 2022)
Viewing the cAbbasid Revolution and the Iranian Revolution from a comparative perspective is the focus of this study. The cAbbasid Revolution was the first Islamic revolution, and the Iranian Revolution is the most recent Islamic revolution, both of which occurred in Muslim societies and practically began in the same geographical area. Although more than twelve centuries separate the two revolutions, similarities exist between them. Both produced profound results, and similar lessons may be culled from them. The first revolution toppled the house of the Umayyads and established a new dynasty. The second overbalanced the House of the Pahlavis and evolved Iran from a monarchy into an Islamic republic. The political role of merchants and their cooperation with religious leaders based on mutual self-interests in both revolutions was a significant factor. Conclusions may be drawn as to when or whether there were changes to Islamic values. These changes may have led to a change in Muslims’ experiences, which can be developed, into the form of a revolution or any type of violence. Taking a comparative methodological approach, this study attempts to make a link between the Iranian Revolution and its cAbbasid past.